Saluran Pemasaran Cabai Rawit di Desa Pucuk Kecamatan Dawarblandong Kabupaten Mojokerto - Septiyan Dwiki Nandika; Mubarokah Mubarokah; Gyska Indah Harya (JURNAL PERTANIAN, 2025)
Bird’s eye chili is a high-value horticultural commodity and plays a significant role in supporting farmers' income. Pucuk Village, Dawarblandong District, Mojokerto Regency, is one of the main production areas with high productivity. However, farmers in this area still face marketing issues, particularly long distribution channels and limited access to market price information. This study aims to identify the marketing channels of bird’s eye chili, calculate marketing costs and margins, and analyze efficiency and farmer’s share in each channel. Data were collected from 50 farmers and 14 traders selected purposively. Quantitative analysis was conducted using formulas for margin, marketing costs, efficiency, and farmer’s share. The results revealed three marketing patterns: (1) farmer – retailer –consumer, (2) farmer–collector–retailer–consumer, and (3) farmer–wholesaler–collector – retailer–consumer. The first channel had the highest efficiency and a farmer’s share above 80%. In contrast, the longest channel provided higher margins for intermediaries but reduced the share received by farmers. In conclusion, shorter marketing channels are more efficient and beneficial for farmers. Therefore, strengthening farmer institutions and improving direct access to markets are essential to shorten the distribution chain.